Feeding Monensin to yearling cattle on summer grass - E.F. Smith; R. Pruitt; Jack G. Riley; L. Corah; Clenton E. Owensby (Kansas Agricultural Experiment Station Research Reports, 1978)
The feed additive, Monensin, was self-fed in a feed block to yearling cattle on summer pasture. Consumption of the block (0.29 lb. daily) supplied 116 mg. of Monensin daily, which failed to improve the cattle's performance.
Keywords: Cattlemen& #x27; s Day; 1978; Report of progress (Kansas State University. Agricultural Experiment Station); 320; Beef; Monensin; Yearling cattle